2021
DOI: 10.1242/dev.199561
|View full text |Cite
|
Sign up to set email alerts
|

Global proteomic analyses of human cytotrophoblast differentiation/invasion

Abstract: During human pregnancy, cytotrophoblasts (CTBs) from the placenta differentiate into specialized subpopulations that play critical roles in proper fetal growth and development. A subset of these CTBs differentiate along an invasive pathway, penetrating the decidua and anchoring the placenta to the uterus. A critical hurdle in pregnancy is the ability of these cells to migrate, invade, and remodel spiral arteries, ensuring adequate blood flow to nourish the developing fetus. While advances continue in describin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 94 publications
(120 reference statements)
0
3
0
Order By: Relevance
“…Based on the above and on the expression of the syncytiotrophoblast markers KISS1 [ 107 ] and SPINT1 [ 108 ] ( Figure 5 A), cells in cluster 11 were identified as SCT. These cells highly expressed cytokeratin genes, such as KRT8 , KRT18 , KRT17 and KRT19 ( Figure 5 B), which have also been described as trophoblast markers [ 109 , 110 , 111 ]. Using GO enrichment analysis of the gene sets representing each of the placental cell clusters, we observed that cells in cluster 11 demonstrated gene sets associated with epithelial cell phenotype and placenta development ( Figure 5 C).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above and on the expression of the syncytiotrophoblast markers KISS1 [ 107 ] and SPINT1 [ 108 ] ( Figure 5 A), cells in cluster 11 were identified as SCT. These cells highly expressed cytokeratin genes, such as KRT8 , KRT18 , KRT17 and KRT19 ( Figure 5 B), which have also been described as trophoblast markers [ 109 , 110 , 111 ]. Using GO enrichment analysis of the gene sets representing each of the placental cell clusters, we observed that cells in cluster 11 demonstrated gene sets associated with epithelial cell phenotype and placenta development ( Figure 5 C).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with studies on TAMs, studies on dMφ are limited to the mice models ( 152 , 153 ), which cannot represent authentic dMφ’s dynamic change along with the human pregnancy, and, due to ethical issues and technical difficulty, it is often infeasible to acquire abundant clinical samples. However, emerging and promising technologies including organoids, microfluidics, and organ-on-a-chip are paving the way for a deeper investigation of vasculogenesis involved in placental development and tumorigenesis ( 154 , 155 ). The effect of TAM and dMφ on vasculature remodeling is illustrated in Figure 4 .…”
Section: Macrophages In Angiogenesismentioning
confidence: 99%
“…So far, the effect of EGCG on the protein expression in trophoblast cells remains unclear. A proteomics analysis is a useful approach for unraveling the mechanisms underlying the various activities of EGCG [ 18 ]. It has been used to analyze the EGCG-regulated proteins in many types of cells, demonstrating that EGCG can regulate and target different sets of proteins that are dependent on different cell types and different experimental conditions [ 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%